Competition Between Organizational Groups: Its Impact on Altruistic and Antisocial Motivations - Goette, Lorenz; Huffman, David; Meier, Stephan; Sutter, Matthias (Management Science, 2012)
Firms are often organized into groups. Group membership has been shown empirically to have positive effects, in the form of increased prosocial behavior toward in-group members. This includes an enhanced willingness to engage in altruistic punishment of inefficient defection. Our paper provides evidence of a dark side of group membership. In the presence of cues of competition between groups, a taste for harming the out-group emerges: punishment ceases to serve a norm enforcement function, and instead, out-group members are punished harder and regardless of whether they cooperate or defect. Our results point to a mechanism that might help explain previous mixed results on the social value of punishment, and they contribute to understanding the sources of conflict between groups. They also point to an important trade-off for firms: introducing competition enhances within-group efficiency but also generates costly between-group conflict. This paper was accepted by Teck Ho, decision analysis.